“Españoles descendientes de aquéllos [indios]”. Nietos españoles de caciques indios - Felipe Canuto Castillo (Nuevo mundo - Mundos Nuevos, 2017)
Mestizaje, or inter-racial unions, between indigenous and Spanish nobility during colonial New Spain, allowed descendants to employ both ethnicities as they saw fit. In eighteenth century documents, for example, these individuals claimed to be Spanish but recognized and documented their indigenous ancestry to legitimize their possessions : they are the so-called Spanish grandchildren of Indians. In this paper, we analyze the case of Eugenio Martínez de Alpízar, descendant of Don Juan Bautista Valerio de la Cruz, Cacique, or chief, conqueror of the 16th century, who during an inheritance trial "clearly asserted his Spanish quality".In this work, we approximate the ethnicity of the Martínez de Alpízar : first, we observe the ethnic composition and the pattern that followed in terms of ethnicity. In the case of Eugenio, it is observed that the “biological ethnicity” was not at odds with the sociocultural, which allowed him to defend his rights as an Indian. To carry out the study we consulted archival documents and we base the study on the genealogy which was developed during that process.